IMPLEMENTASI PENDEKATAN SAINTIFIK DAN PENILAIAN OTENTIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SMAN 7 BOGOR - Nadya Putri Saylendra; Endang Danial (Jurnal Ilmiah Mimbar Demokrasi, 2015)
This research is purposed to know how the implementation of scientific approach and authentic assessment in civics and citizenship in SMAN 7 Bogor. This research employed a descriptive methods from qualitative research.The results showed that teacher has understanding on the scientific approach and authentic assessment in the study of civic education. The planning of scientific approach and authentic assessment in civic education has been carried out thoroughly. The implementation of scientific approach and authentic assessment in study of civic and citizenship, the teacher has demonstrated the stages of scientific approach and processing score into value using the existing assessment format. The scientific approach and authentic assessment showed an objective results of student learning competencies; such as attitude, skills and knowledge.